Relationship of Knowledge of Postpartum Mothers With Interest in The Installation Of Intrauterine Devices (IUD) in 2021 - Fatma Adriani; Puspita Adriani; Mashuri Posimbi (JURNAL KEBIDANAN KESTRA (JKK), 2022)
One of the factors that have an impact on increasing maternal mortality (AKI) is the risk of 4 too. The percentage of mothers who die who give birth under the age of 20 years and over 35 years is 33% of all maternal deaths, so if the birth control program can be implemented properly again, likely 33% of maternal deaths can likely be prevented through the use of contraception. This research aims to know relations knowledge of mothers' Post Partum with an interest in Installing Intrauterine Devices s (IUD) in the Unaaha Health Center Working Area. Type of analytical research with cross-sectional. The population in this study was all Post Partum mothers in October 2021 with a sample number of 30 people. Showed enough knowledge as 13 respondents (43.3%), knowledgeable as many as 9 respondents (30%), and knowledgeable less than as many as 8 respondents (26.7%). While those who are interested in installing AKDR as many as 17 respondents (56.7) and those who are not interested as many as 13 respondents (43.3%). Based on the results of the chi-square test, the test shows p-value = 0.009, so that the p-value is 0.009< ? = 0.05. There is a relationship between mothers' Post Partum knowledge and their Interest in Intrauterine Devices s (IUD) in the Unaaha Health Center Working Area in 2021.